2021
DOI: 10.1002/ecs2.3529
|View full text |Cite
|
Sign up to set email alerts
|

Size‐, species‐, and site‐specific tree growth responses to climate variability in old‐growth subalpine forests

Abstract: Tree-ring data have become widely used to model tree growth responses to climate variability and gain insight about the potential effects of global warming on forests. We capitalized on a rare opportunity to develop growth-climate models using tree-ring data collected from all trees (>4 cm in diameter at breast height) within 50 × 50 m plots established in subalpine old-growth forests of western Canada. Our objective was to determine how tree growth responses to climate vary among tree size classes, species, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 108 publications
(202 reference statements)
0
8
1
Order By: Relevance
“…We also provided an example in which climate change facilitates a range expansion of ancient tea trees. This is inconsistent with previous studies indicating the negative effects of climate change on trees and forests [22,51]. Hence, climate change's effects on different species and the effects of different temperature bands are worth exploring.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…We also provided an example in which climate change facilitates a range expansion of ancient tea trees. This is inconsistent with previous studies indicating the negative effects of climate change on trees and forests [22,51]. Hence, climate change's effects on different species and the effects of different temperature bands are worth exploring.…”
Section: Discussioncontrasting
confidence: 90%
“…Many studies have suggested that the diversity and density of ancient trees are affected by climate [22][23][24], landform [25,26], soils [27], and disturbance [28,29], which are the main environmental factors affecting the niches and distributions of plants [30]. Previous studies have also indicated that climate change [31] and management approaches [32] can have a substantial effect on the niches and distributions of species.…”
Section: Introductionmentioning
confidence: 99%
“…We considered tree identity ( Z hk B hk ) as a random effect. We also included an error term ( ) with a first-order autoregressive (AR1 [ P = 1, q = 0] correlation structure, which is usually sufficient to account for legacy effects on current year growth increment ( 71 ). The smoothing term, s , represents a cubic regression spline for which the degree of smoothness was determined through an iterative fitting process ( 69 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our models, climate explained only a small proportion of year-to-year variance in ring-width indices for each species, despite the significant correlations of yellow-cedar and western hemlock with climate. Similarly, Campbell et al (2021) also found low growth variance explained by climate in Pacific coastal forests containing yellow-cedar and western hemlock. The low explanatory power of our chosen climate variables may have been due to the temperate, ocean-moderated climate or relatively strong influences of local site conditions or gap dynamics inherent to old growth forests.…”
Section: Climate and Tree Growth Responses Differed Among Pacific Decadal Oscillation Phasesmentioning
confidence: 79%